Heterogeneous Olefin Hydrogenation Enabled by a Highly‐Reduced Nickel(−II) Catalyst Precursor - Maier, Thomas M. (Chemistry, 2020)
The hydrogenation of olefins, styrenes, enoates, imines, and sterically hindered tri‐substituted olefins was accomplished using the pre‐catalyst dilithiumbis(cycloocta‐1,5‐diene)nickelate(−II) (1). The mild conditions tolerate hydroxyl, halide, ester, and lactone functionalities. Mechanistic studies, including reaction progress analyses, poisoning experiments, and multinuclear NMR monitoring, indicate that a heterotopic (nickel nanoparticle) catalyst is in operation.